2018
DOI: 10.1242/jeb.159277
|View full text |Cite
|
Sign up to set email alerts
|

The locomotor kinematics and ground reaction forces of walking giraffes

Abstract: Giraffes (Giraffa camelopardalis) possess specialised anatomy. Their disproportionately elongate limbs and neck confer recognised feeding advantages, but little is known about how their morphology affects locomotor function. In this study, we examined the stride parameters and ground reaction forces from three adult giraffes in a zoological park, across a range of walking speeds. The patterns of GRFs during walking indicate that giraffes, similar to other mammalian quadrupeds, maintain a forelimb-biased weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 45 publications
9
63
0
Order By: Relevance
“…The three lines can be generated by following three simple rules in symmetrical walking gaits: The horse pattern ( D = percentage duration of forelimb swing phase = 100 − S f : Figure a) results from following the rule “Lift each forefoot when the hindfoot on that side touches down.” This pattern, which is approximated in the symmetrical walking gaits of most quadrupeds, minimizes periods of bipedal support in LC‐DS walking gaits, in which diagonality values lie between 25 (the LS amble or singlefoot; Schmitt, Cartmill, Griffin, Hanna, & Lemelin, ) and 50 (the trot). Its equation graphs a negative linear relationship of D against S (duty factor), with a slope of −1. The monkey pattern ( D = S h : Figure b), characteristic of quadrupedal primates, results from following the rule “Lift each hind foot when the fore foot on that side touches down.” This pattern minimizes periods of bipedal support in DC‐DS walking gaits, in which diagonality values lie between 50 (the trot) and 75 (the DS amble). The camel pattern ( D = S h − 50: Figure c), around which the gaits of camelids, giraffes (Basu, Wilson, & Hutchinson, ), pacing horses, and many carnivorans cluster, obeys the rule “Lift each hindfoot when the forefoot on the opposite side touches down.” This pattern minimizes periods of bipedal support in LC‐LS walking gaits, in which diagonality values lie between 0 (the pace) and 25 (the LS amble). Both the camel and monkey equations generate lines with a positive relationship between D and S, with slopes of +1 on the Hildebrand diagram, displaced from each other by a phase shift of 180° (50%) on the diagonality axis. …”
Section: Introductionmentioning
confidence: 98%
“…The three lines can be generated by following three simple rules in symmetrical walking gaits: The horse pattern ( D = percentage duration of forelimb swing phase = 100 − S f : Figure a) results from following the rule “Lift each forefoot when the hindfoot on that side touches down.” This pattern, which is approximated in the symmetrical walking gaits of most quadrupeds, minimizes periods of bipedal support in LC‐DS walking gaits, in which diagonality values lie between 25 (the LS amble or singlefoot; Schmitt, Cartmill, Griffin, Hanna, & Lemelin, ) and 50 (the trot). Its equation graphs a negative linear relationship of D against S (duty factor), with a slope of −1. The monkey pattern ( D = S h : Figure b), characteristic of quadrupedal primates, results from following the rule “Lift each hind foot when the fore foot on that side touches down.” This pattern minimizes periods of bipedal support in DC‐DS walking gaits, in which diagonality values lie between 50 (the trot) and 75 (the DS amble). The camel pattern ( D = S h − 50: Figure c), around which the gaits of camelids, giraffes (Basu, Wilson, & Hutchinson, ), pacing horses, and many carnivorans cluster, obeys the rule “Lift each hindfoot when the forefoot on the opposite side touches down.” This pattern minimizes periods of bipedal support in LC‐LS walking gaits, in which diagonality values lie between 0 (the pace) and 25 (the LS amble). Both the camel and monkey equations generate lines with a positive relationship between D and S, with slopes of +1 on the Hildebrand diagram, displaced from each other by a phase shift of 180° (50%) on the diagonality axis. …”
Section: Introductionmentioning
confidence: 98%
“…At walking speeds, giraffes use a lateral sequence walk, which is dynamically similar to the slow gaits of other mammalian quadrupeds (Basu et al 2018). The theory of dynamic similarity predicts that geometrically similar animals move with similar dimensionless stride parameters at equivalent dimensionless speeds.…”
Section: Gait Dynamics In Giraffes and Other Quadrupedal Mammalsmentioning
confidence: 93%
“…Based on observations of other mammalian quadrupedal gaits (Hildebrand 1976) and predictive modelling of quadrupedal footfall sequences (Cartmill et al 2002), giraffes are expected to select a running pace as their intermediate gait. A study involving simulations of quadrupedal gaits also suggested that giraffes will select a pacing gait at intermediate speeds (Suzuki et al 2016); however this model inaccurately predicted that giraffes use a diagonal sequence walk at slow speeds, contrasting with the experimentally observed lateral sequence walk (Basu et al 2018). Giraffes instead seemingly transition consistently from a walk to a rotary gallop (Dagg & Vos 1968;Maxwell 1924).…”
Section: Eqn 1 = 2 ℎmentioning
confidence: 99%
See 2 more Smart Citations